THE IMPACT OF INFORMATION QUALITY, PROCESS QUALITY, AND SERVICE QUALITY TOWARDS ORGANIZATIONAL PERFORMANCE THROUGH ORGANIZATIONAL INNOVATIVENESS ON BEAUTY CLINICS IN SURABAYA - Gunawan, Hananiel Mennoverdi (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This research investigates the intricate interplay between information quality, process quality, service quality, innovativeness, and organizational performance within the context of beauty clinics in Surabaya. Drawing upon a mixed-methods approach, data is gathered from a diverse sample of beauty clinics. The study aims to discern the extent to which information quality influences the quality of processes adopted by beauty clinics and how this, in turn, impacts service quality. Furthermore, the research delves into how service quality and the overall competitiveness of beauty clinics mediate the relationship between information quality, process quality, and organizational performance. Surabaya, a vibrant cosmopolitan hub, serves as an ideal setting for this inquiry due to its burgeoning beauty industry and competitive market landscape. The findings are expected to provide valuable insights for beauty clinic operators, policymakers, and researchers alike, offering actionable recommendations to enhance organizational performance through strategic improvements in information management, process optimization, and service delivery. Ultimately, this study seeks to contribute to the existing literature on organizational innovativeness and performance within the beauty industry while offering practical implications for stakeholders navigating the dynamic business environment in beauty clinic in Surabaya.